Telaah Kritis Pasal 7 Undang-Undang No.16 Tahun 2019 Tentang Perkawinan - Elfirda Ade Putri (Jurnal Hukum Sasana, 2021)
Marriage is also regulated in Article 28B Paragraph 1 of the 1945 Constitution which states "Everyone has the right to form a family and continue their descendants through legal marriage". In Article 26 of the Civil Code, views the matter of marriage only in civil relations. This means that the law recognizes civil marriages as legal marriages, i.e. marriages that meet religious requirements or provisions are not given much attention or neglected. Meanwhile, according to the Compilation of Islamic Law Article 2 states that marriage is a marriage, a very strong contract or Miitsaaqan Gholiidhzan which aims to obey Allah's commands and carry out a worship. Based on statistical data and studies that have been done, early marriage is still a social problem in Indonesia. BAPPENAS data shows 34.5% of Indonesian children marry early. This data is corroborated by the PLAN International study which showed 33.5% of children aged 13 ± 18 years were married at the age of 15-16 years. Early marriage inhibits the growth and development of children, both biologically and psychologically. Early marriage has an impact on the deprivation of children's rights because they are forced to enter the adult world instantly. Early marriage in Indonesia is motivated by many factors, such as the low level of the family's economy, low education, lack of knowledge and education and the most prevalent is pregnancy out of wedlock.